Model Development with Buddha Teaching’s Determination of Sangha in 26th Buddhist era Century - Sripariyutthayanusat, Phrakhru; (Petlert), Phraathikan Thammanoon; Chueram, Wai (Dhammathas Academic Journal, 2019)
The research aims to: 1) to study the method of propagation of Buddhist monk in 26th century; 2) to study affecting the propagation of Buddhism in the 26 th century. the sample of monks in Buriram. Used the Taro Yamane furmula. The 399 samples were collected in Buriram province. The research was a question naire. Statistics used for data analysis in clouding frequency distribution, mean, standard deviation, regression, multiple regression (multiple Regression Analysis). The research aims to: 1) to study the method of propagation of Buddhist monk in 26th century; 2) to study affecting the propagation of Buddhism in the 26 th century. the sample of monks in Buriram. Used the Taro Yamane furmula. The 399 samples were collected in Buriram province. The research was a question naire. Statistics used for data analysis in clouding frequency distribution, mean, standard deviation, regression, multiple regression (multiple Regression Analysis). The results of study were found that: the level of Buddhist Propaganda of Buddhist monks in the 26th century was at a high level. ( = 3.62, S.D. = 0.54). Factors affecting the Buddhist Propaganda of Buddhist monks in the 26 centery were statistically significant at the .05 level. The factor is the ability in the psychology of knowledge in the context. Performance factors and techniques for Buddha fhamma propagation. Potential factor of the monks artistic factor in the transmission all 10 factors.